Trouble with Initial Value Condition Questions

I have been looking at an example of a initial value condition problem in my notes and don't really understand where the solution came from. Here is the question:

Let z(x,y)= 2x+ g(xy) and add the initial value conditon, z= x on the line y=1. Find the general solution of the initial value problem.


1. Replace z(x,y)=2x+g(xy) wih the condition to get x= 2x+g(x) for all x, so that g(x)= -x

I understand everything so far but then the next step says "hence z(x,y)= 2x-xy is the general solution." Where does the -xy come from?

Any help or advice would be much appreciated! Thank you
 

Simon Bridge

Science Advisor
Homework Helper
17,823
1,637
Can you find another relation that would fit the conditions?
 

HallsofIvy

Science Advisor
Homework Helper
41,721
876
It's just a matter of the "functional notation" you have been using for years:

If g(x)= -x then g(u)= -u, g(a)= -a, g(v)= -v, etc.

In eactly the same way, g(xy)= -xy.
 
OK I understand now, thank you
 

Related Threads for: Trouble with Initial Value Condition Questions

Replies
1
Views
2K
  • Posted
Replies
8
Views
2K
  • Posted
Replies
7
Views
2K
Replies
2
Views
2K
  • Posted
Replies
13
Views
4K
Replies
4
Views
505
Replies
2
Views
2K
Replies
1
Views
3K

Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving

Hot Threads

Top